Predicting response to cardiac resynchronization therapy: Use of strict left bundle branch block criteria. Issue 4 (28th February 2019) - Hadjis, Alexios; AlTurki, Ahmed; Proietti, Riccardo; Montemezzo, Mauricio; Bernier, Martin; Joza, Jacqueline; Hadjis, Tomy; Essebag, Vidal
Abstract: Background: Cardiac resynchronization therapy (CRT) reduces morbidity and mortality in heart failure with reduced ejection fraction (HFrEF). CRT efficacy is greater in left bundle branch block (LBBB). This study aimed to determine if strict LBBB criteria predict an improved QRS duration and left ventricular ejection fraction (LVEF) response after CRT. Methods: HFrEF patients who received a CRT device at a single quaternary center were included. Patients were divided into three groups based on baseline QRS morphology. Group 1 consisted of patients with strict LBBB. Group 2 had conventional LBBB, and group 3 had non‐LBBB morphology. Outcomes assessed included change in QRS duration after CRT, change in LVEF, and all‐cause mortality. Results: In 231 patients, 56% of patients were in group 1, 29% were in group 2, and 15% were in group 3. Patients with strict LBBB had a significant reduction in QRS duration (–20.9 ± 12.4 ms) compared to conventional LBBB (6.7 ± 19.4 ms; P < 0.0001) and non‐LBBB (3.9 ± 29.3 ms; P < 0.0001). Patients with strict LBBB had a significant increase in LVEF (19.5 ± 10.2) compared to conventional LBBB (5.3 ± 12.6; P < 0.0001) and non‐LBBB (–1.3 ± 10.9; P < 0.0001). There was moderate negative correlation between changes in QRS duration and LVEF (correlation coefficient = –0.63, P < 0.0001). Strict LBBB criteria were associated with a significant reduction in mortality compared to conventional LBBB (odds ratio 0.49, 95% confidence interval 0.24 to 0.99; P = 0.046). Conclusions: Strict LBBB predicted a reduction in QRS duration and an increase in LVEF compared to conventional LBBB and non‐LBBB morphology in patients with HFrEF who received CRT.